2022
DOI: 10.1093/jncics/pkac048
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of a Telephone-Based Smoking Cessation Randomized Trial in the Lung Cancer Screening Setting

Abstract: Background There are limited data on the cost-effectiveness of smoking cessation interventions in lung cancer screening settings. We conducted an economic analysis embedded in a national randomized trial of two telephone counseling cessation interventions. Methods We used a societal perspective to compare the short-term cost per 6-month bio-verified quit and long-term cost-effectiveness of the interventions. Trial data were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…The incremental costs per QALY gained were estimated to be larger with the 8-weeks intensive counselling. 47 Results from our current review, suggest that providing more support (multiple counselling sessions and pharmacotherapy) compared with less-intensive approaches, may be more favourable for a screening population. However, there were only limited direct comparison data, leading to only a recommendation of moderate certainty.…”
Section: Discussionmentioning
confidence: 80%
“…The incremental costs per QALY gained were estimated to be larger with the 8-weeks intensive counselling. 47 Results from our current review, suggest that providing more support (multiple counselling sessions and pharmacotherapy) compared with less-intensive approaches, may be more favourable for a screening population. However, there were only limited direct comparison data, leading to only a recommendation of moderate certainty.…”
Section: Discussionmentioning
confidence: 80%
“…For example, our remote research protocols for recruitment, interviewing, and surveying can be replicated at relatively low cost in future studies designed to examine longer periods of mindfulness training or mindfulness training combined with pharmacotherapy, such as nicotine replacement therapy. In support of this future aim, previous studies have identified telehealth approaches (eg, delivery of quit-smoking counseling by telephone) combined with nicotine replacement therapy to be a cost-effective strategy for cessation in clinical settings ( 39 ). Our interpretations of this trial’s results are limited in a few ways.…”
Section: Discussionmentioning
confidence: 96%
“…Results of the RCT showed that delivering intensive telephone counseling and nicotine replacement therapy with lung cancer screening is an effective strategy to increase smoking cessation at month 3 ( 43 ). Moreover, in a cost-effectiveness analysis of the intervention, telephone counseling and nicotine replacement therapy were considered cost-effective in lung cancer screening settings ( 44 ). Integrating smoking cessation interventions with lung screening programs has the potential to maximize long-term health benefits at reasonable costs.…”
Section: Discussionmentioning
confidence: 99%